Exploitation of Interleukin-8-Induced Neutrophil Chemotaxis by the Agent of Human Granulocytic Ehrlichiosis - Akkoyunlu, Mustafa (American Society for Microbiology, 2001)
The agent of human granulocytic ehrlichiosis (HGE) is an obligate intracellular bacterium with a tropism for neutrophils; however, the mechanisms of bacterial dissemination are not yet understood. Interleukin-8 (IL-8) is a chemokine that induces neutrophil migration to sites of infection for host defense against pathogens. We now show that HGE bacteria, and the HGE-44 protein, induce IL-8 secretion in a promyelocytic (HL-60) cell line that has been differentiated along the neutrophil lineage with retinoic acid and in neutrophils. Infected HL-60 cells also demonstrate upregulation of CXCR2, an IL-8 receptor, but not CXCR1. Human neutrophils migrate towards Ehrlichia sp.-infected cells in a chemotaxis chamber assay, and this movement can be blocked with antibodies to IL-8. Finally, immunocompetent and severe combined immunodeficient mice administered CXCR2 antisera, and CXCR2(−/−) mice that lack the human IL-8 receptor homologue, are much less susceptible to granulocytic ehrlichiosis than are control animals. These results demonstrate that HGE bacteria induce IL-8 production by host cells and, paradoxically, appear to exploit this chemokine to enhance infection.